Superficial Mycoses - Fatma Rosida; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Superficial mycoses were superficial fungal infections caused by fungal or yeast colonization. The prevalence of fungal infection is estimated 20-25% of the world’s population and one of the most common infection in humans. Purpose: To evaluate the profile of superficial mycoses patients. Method: A retrospective study of all new cases of superficial mycoses who visited the Mycology Division, Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya from January 2011 until December 2013 (3 years). Results: The total new patients in 2011-2013 was 1.136 with the percentage 5,47% in 2011, 4,91% in 2012, and 5,90% in 2013. Men were more affected than women, and it was more common in the age group 15-24 and 25-44. Most patients complaint were itchy and most commonly used therapies were ketoconazole 200 mg and griseofulvin 125 mg orally. Conclusion: Superficial mycoses is still a common issue in Indonesia, especially in Surabaya.